Gamification intervention in teaching and learning accounting: ComAcc Card / Nur Syafiqah Hussin, Naqiah Awang and Nurul Afzan Najid - Hussin, Nur Syafiqah; Awang, Naqiah; Najid, Nurul Afzan (UiTM Cawangan Johor, 2019)
Gamification is expected to make students hooked by the idea of the game and make them engaged in the game's idea and activity, which eventually allows for the possibility of learning process. The features of the game encourage curiosity and exploration to enhance engagement and improve content comprehension. Eventually, students will be rewarded with knowledge and skills that the game offered. The game called as ComAcc Card was triggered by the importance of students to be able to understand the components in financial statements. Failure to do so will affect the process of preparation of financial statements which is part of the course requirements. The game is expected to encourage positive student attitudes in the learning process and strengthen the students' ability to classify items according to its components in accounting. Thus, the paper presents a simple method of accounting card game introduced to the non-accounting students, and it disucsses students' perception towards the use of gamification in teaching and learning process.